ANALISIS TINGKAT KESEHATAN PERUSAHAAN BUMN BIDANG KONSTRUKSI BERDASARKAN SURAT KEPUTUSAN MENTERI BUMN NOMOR: KEP-100/MBU/2002 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2012-2016 - Santoso, Mayasari (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the health level of state-owned enterprises working in construction sector listed in the IDX during the period of 2012-2016. Their health is assessed from their financial aspect based on the decree of the Minister of SOE number KEP-100/MBU/2002. There are 8 ratios that are used to assess their health; they are ROE, ROI, CR, CAR, CP, ITO, TATO, and Equity to TA.The population of this descriptive quantitative study is four state-owned construction companies listed in the IDX. Using saturated sampling technique, the entire population is selected as the sample.The results show that the ROI of the state-owned construction companies is the lowest of all eight ratios. During the period of 2012-2016, most of the companies are in the category A with healthy predicate. Based on the results of the study, the companies are expected to improve their financial health to obtain the predicate of healthy in category AAA. It is essential for the them to improve their financial performance because they have a duty to improve the welfare of Indonesian people. The companies are showing a stable trend and have a good performance.Keywords: health level, state-owned enterprise, construction company, financial ratios, financial performance, decree of Minister of SOE number KEP-100/MBU/2002